Regional developments [In 2018 Global food policy report] - Makombe, Tsitsi; Collins, Julia; Ulimwengu, John M.; Badiane, Ousmane; Breisinger, Clemens; Abdelaziz, Fatma; Khouri, Nadim; Akramov, Kamiljon T.; Ilyasov, Jarilkasin; Park, Allen; Kumar, Anjani; Ahmed, Akhter; et al. (International Food Policy Research Institute, 2018)
At the regional and country level, developments in 2017 had important repercussions for food security and nutrition. This section offers perspectives on food policy developments across the major regions: Africa, the Middle East and North Africa, Central Asia, South Asia, East and Southeast Asia, and Latin America and the Caribbean. Globalization and the impact of growing antiglobalization pressures on food security are examined for each region, along with many other current topics.